Keragaan Varietas Unggul Baru Padi Khusus Inpari IR Nutri Zinc di Kutai Kartanagera Provinsi Kalimantan Timur - Asep Pebriandi; Sulhan Sulhan; Setyawan Setyawan (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Apart from being a source of energy, rice has health benefits. Rice contains minerals that function for the growth and development of several vital organs. The purpose of this study was to determine the performance of the new high-yielding variety Inpari IR Nutri Zinc. This research was conducted in the rice fields of the Cempaka farmer group and the Lestari farmer group, Bukit Raya village, Samboja District, Kutai Karatanegara, East Kalimantan. The study was conducted from December 2020 to March 2021. This study was conducted using a randomized block design (RAK) with 5 (five) replications. The treatments used were Inpari IR Nutri Zinc, Inpari 32 HDB, and Bion iAgritan Ciherang. Data analysis with analysis of variance test, if significantly different, continued with 5% BNT further test. The results showed that Inpari IR Nutri Zinc produced higher rice productivity, namely 6.91 tons/ha GKP when compared to Inpari 32 HDB and Bion 63 Ciherang Agritan varieties. This shows that the new high-yielding variety of Inpari IR Nutri Zinc is adaptive when it is developed in Kutai Kartanegara Regency, East Kalimantan Province.